Respuesta :
For this case we have the following expression:
[tex]v = pir ^ 2h [/tex]
Substituting values we have:
[tex]v = pi (x + 8) ^ 2 (2x + 3) [/tex]
Rewriting we have:
[tex]v = pi (x ^ 2 + 16x + 64) (2x + 3) v = pi ((2x ^ 3 + 32x ^ 2 + 128x) + (3x ^ 2 + 48x + 192)) [/tex]
[tex] v = pi (2x ^ 3 + 35x ^ 2 + 176x + 192) v = (2pix ^ 3 + 35pix ^ 2 + 176pix + 192pi)[/tex]
Answer:
An expression that represents the volume of the can is:
c) 2 pie x^3 + 35 pie x^2 +176 pie x + 192 pie
[tex]v = pir ^ 2h [/tex]
Substituting values we have:
[tex]v = pi (x + 8) ^ 2 (2x + 3) [/tex]
Rewriting we have:
[tex]v = pi (x ^ 2 + 16x + 64) (2x + 3) v = pi ((2x ^ 3 + 32x ^ 2 + 128x) + (3x ^ 2 + 48x + 192)) [/tex]
[tex] v = pi (2x ^ 3 + 35x ^ 2 + 176x + 192) v = (2pix ^ 3 + 35pix ^ 2 + 176pix + 192pi)[/tex]
Answer:
An expression that represents the volume of the can is:
c) 2 pie x^3 + 35 pie x^2 +176 pie x + 192 pie
input
V=pi(x+8)^2(2x+3)
V=pi(x^2+16x+64)(2x+3)
V+pi(2x^3=35x^2+176x+192)
V=2πx³+35πx²+176πx+192π
V=pi(x+8)^2(2x+3)
V=pi(x^2+16x+64)(2x+3)
V+pi(2x^3=35x^2+176x+192)
V=2πx³+35πx²+176πx+192π